Crystal Structure and Catalytic Behavior in Olefin Epoxidation of a One-Dimensional Tungsten Oxide/Bipyridine Hybrid - Amarante, Tatiana R.
The tungsten oxide/2,2'-bipyridine hybrid material [WO3(2,2'-bpy)]center dot nH(2)O (n = 1-2) (1) has been prepared in near quantitative yield by the reaction of H2WO4, 2,2'-bpy, and H2O in the mole ratio of ca. 1:2:700 at 160 degrees C for 98 h in a rotating Teflon-lined digestion bomb. The solid-state structure of 1 was solved and refined through Rietveld analysis of high-resolution synchrotron X-ray diffraction data collected for the microcrystalline powder. The material, crystallizing in the orthorhombic space group Iba2, is composed of a one-dimensional organic-inorganic hybrid polymer, (1)(infinity)[WO3(2,2'-bpy)], topologically identical to that found in the previously reported anhydrous phases [MO3(2,2'-bpy)] (M = Mo, W). While in the latter the N,N'-chelated 2,2'-bpy ligands of adjacent corner-shared MO4N2 octahedra are positioned on the same side of the 1D chain, in 1 the 2,2'-bpy ligands alternate above and below the chain. The catalytic behavior of compound 1 for the epoxidation of cis-cyclooctene was compared with that for several other tungsten- or molybdenum-based (pre)catalysts, including the hybrid polymer [MoO3(2,2'-bpy)]. While the latter exhibits superior performance when tert-butyl hydropercndde (TBHP) is used as the oxidant, compound 1 is superior when aqueous hydrogen peroxide is used, allowing near-quantitative conversion of the olefin to the epoxide. With H2O2, compounds 1 and [MoO3(2,2'-bpy)] act as sources of soluble active species, namely, the oxodiperoxo complex [MO(O-2)(2)(2,2'-bpy)], which is formed in situ. Compounds 1 and [WO(O-2)(2)(2,2'-bpy)] (2) were further tested in the epoxidation of cydododecene, trans-2-octene, 1-octene, (R)-limonene, and styrene. The structure of 2 was determined by single-crystal X-ray diffraction and found to be isotypical with the molybdenum analogue.